Intracochlear Hemorrhage: A Rare Cause of Sudden Sensorineural Hearing Loss. (22nd November 2021) - Jrad, Myriam; Zlitni, Haifa; Boumediene, Miriam; Nasr, Atef Ben; Bouzrara, Meriem
Abstract : Inner ear hemorrhage is an extremely rare cause of sudden sensorineural hearing loss with few cases reported in the literature. We report the case of a 30-year-old male who presented with a sudden left ear hearing loss, with no tinnitus nor vertigo. The audiogram revealed a profound left sensorineural hearing loss. An MRI of the brain and internal auditory canal was performed 3 weeks after and revealed an increased signal intensity on T1-weighted (T1W) and T2 fluid-attenuated inversion recovery (FLAIR) images in the left cochlea. No other abnormalities were found, in particular no enhancement after intravenous administration of gadolinium. The CISS 3D sequence showed a signal of discreetly lower intensity in the left cochlea compared to the right one. The diagnosis of intracochlear hemorrhage was made. No improvement of the hearing loss has been noted after medical treatment and hyperbaric oxygen therapy.